Penyuluhan dan Pemeriksaan Kadar Kolesterol sebagai Upaya Pencegahan Penyakit Kolesterol pada Lansia di Pekon Gadingrejo Utara, Kecamatan Gadingrejo, Kabupaten Pringsewu - Abdul Karim, Dewi Damayanti; Dirga; Sarmoko; Novrilia Atika Nabila; Imam Safei; Charisa Nabirawati Sitindaon; Wenda Reka Pratama; Bama Tangguh Galih; Farhan Fauzan; Tria Putriani; Kireine Kosma Ramadhani; Silvia Damayanti; Adinda Salsabila; Dito Aditya Sasongko; Vigo Atsil Nugraha (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
High cholesterol or hyperlipidemia is a major risk factor for cardiovascular disorders such as coronary heart disease. Managing high cholesterol can involve lifestyle changes and pharmacological treatment, but many people still lack an understanding of the importance of effective cholesterol management. This Community Service activity aims to raise awareness and knowledge about cholesterol, including risk factors, health impacts, and management strategies through community-based health education programs. The methods of this activity include counseling, open discussions, and health screenings. This community service program was conducted in Pekon Gadingrejo Utara, Gadingrejo District, Pringsewu Regency, with a target specifically aimed at the elderly. The results of this activity showed an increase in public understanding of hyperlipidemia, evidenced by an increase in post-test scores from the pre-test (42,6%). In health screenings with 50 participants, 90% were found to have high cholesterol. This activity was deemed effective in increasing community knowledge and identifying the prevalence of hyperlipidemia among the local elderly population.